ANCIENT WINDOW PANE OYSTER BED IN GOA WITH COMPARATIVE NOTES ON THE OYSTER IN AN EXTANT BED - Thomas, P A; Thanapathi, V (Indian Journal of Fisheries, 2011)
A bsd consisting of a liTge quantity of semifossdlised shells of window pane oyster Placenta placenta (Linn.) was discove,red accidently in a paddy field by the side of the river Mandovi ’.n Goa. Subsequent investigations lead to the conclusion that there was a flourishing population of window pane oyster in this rrea prior to the 16th century, and that this rich population perished subsequently as a result of indiscriminate intervention by way of reclamation. This population is compared with that which exiists ft present in the Zuari estuary of Goa. Attempts are also m de to compare the incidence and distribution of .boring sponges among the window pane oyster, both ancient and extant.